PENGARUH MOTIVASI OLEH CAMAT TERHADAP PRESTASI KERJA PEGAWAI DI KANTOR CAMAT KECAMATAN GUNUNG JATI KABUPATEN CIREBON - Mukhamad Makhrus; Heriyani Agustina; Rahmat Hidayat (Jurnal Ilmiah Publika, 2013)
Research by the author of " Influence Motivation By Camats Against Employee Job Performance in the District Head Office Gunung Jati Cirebon " begins with the discovery of a problem that is not achieving optimal performance of the employees allegedly due to lack of motivation by the sub-district . The method used is the survey method , the quantitative descriptive analysis techniques . Methods of survey research that is done on a large or small population , but the data are studied data from samples taken from the population . So the effect is found between variables . While the quantitative descriptive analysis techniques , namely the analysis of research data using statistical tests of non - parametik by using the formula " Spearman rank correlation coefficient " . Sample collection technique that I use is the saturation sampling , which takes all the population to dijadikam sample . Total population is as much as 16 employees . The hypothesis that the authors propose is as follows : " Motivation by sub-district and a significant positive effect on work performance of employees in the District Head Office Gunung Jati Cirebon " . The statistical hypothesis is as follows : Ho ( null hypothesis ) = rs rs ≤ Calculate Table ( no positive and significant relationship between the sub-district Motivation Employee Job Performance ) . Ha ( Alternative Hypothesis ) = rs rs Calculate ˃ table ( there is a positive and significant relationship between the sub-district Motivation Employee Job Performance ) . Based on this research, it turns out that the motivation variable is not optimal , it is visible from a total score of 602 or a percentage of 62.708 % at pretty good levels . Then also less variable performance is achieved , it is seen from the total score of 300 or a percentage of 62.5 % had a level good enough . The authors propose the hypothesis H0 is rejected and Ha accepted rs Calculate the value of both variables at 0.807 and 0.425 Table rs value was significant.